Analisis Progam Mushafahah Sebagai Upaya Pembentukan Karakter Pada Siswa - Hafizul Hamdi; Nurjanah Nurjanah (Prodi Pendidikan Keagamaan Islam, 2024)
Character formation is an important aspect of education in dealing with moral crises among students. Through early character education, students are expected to have polite, respectful, and disciplined attitudes. This research aims to analyze the mushafahah program to build student character in elementary schools. This research uses a qualitative method with a case study approach. Data sources were taken from eight informants, namely one principal, one female teacher, one male teacher, one female staff, two female students, and two male students through in-depth interviews using purposive sampling techniques. Overall, the conclusions of the research results show that 1) There are four contributions of the Mushafahah Program in Efforts to Form the Character of Payakumbuh Muhammadiyah Plus Primary School Students, namely a. forming a harmonious relationship between teachers, students and parents, b. emotional approach with students, c. changes in student behavior, d. they are teaching manners to students. 2) Character aspects formed from the mushafahah program for students a. respectful attitude, b. discipline attitude, c. polite attitude, d. polite attitude.